Financial distress and highway infrastructure delays - Edwards, D.; Owusu-Manu, D.; Baiden, B.; Badu, E.; Love, Peter (Emerald Group Publishing Limited, 2017)
© 2017, © Emerald Publishing Limited. Purpose: In developing countries, delays in highway infrastructure projects caused by financial distress-related factors threaten the construction industry’s capacity to contribute optimally to economic development. Against this backdrop, this paper aims to determine factors contributing to financial distress and develops a conceptual framework to illustrate the relationship between financial distress and project delay. Design/methodology/approach: A questionnaire survey collected data on factors that contributed to financial distress and delays in highway infrastructure delivery. In total, 78 responses were obtained, and factor analysis revealed that factors associated with payment, project financing, cash flow, economic issues, project planning and cost control influenced project delays. Findings: The research identifies the importance of efficient public and private policies to engender financial sustainability among construction firms in developing countries. Originality/value: This work presents the first research of its kind and strives to engender wider academic debate and renewed economic development in some of the world’s most impoverished nations.